(untitled) (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2025)
The article presents a philosophical analysis of the concept of ecological culture and its role in solving environmental problems in society. It explores the factors influencing the formation of ecological culture, including its spiritual, moral, historical, cultural, and religious foundations. The impact of urbanization, technological advancement, and the level of public consciousness on the deepening of ecological issues is discussed. The author highlights the potential for achieving environmental security through the development of ecological culture.